PENGGUNAAN ONOMATOPE DALAM IKLAN SENKA PERFECT WHIP BERBAHASA JEPANG - Nasution, Nurul Aminah; Aibonotika, Arza; Utami, Mutiara Rahmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This study aims to analyze the descriptive use of onomatopoeia in SENKA Perfect Whip advertisements. Onomatopoeia comes from Ancient Greek, namely onomatopeiia which means the formation of names or words that sound like their references. The data used is obtained from advertising texts sourced from several social media. The results of the analysis show that the use of onomatopoeia in advertising, especially in the context of beauty, helps consumers. the use of onomatopoeia that reflects softness, beauty, and moisture creates an image of the atmosphere of Japanese culture. Onomatopoeia is used to describe a situation or a person's personal experience of an object, so using onomatopoeia in advertising creates a visual imagination without sound that describes the impression of slippery, smooth and soft. The touch generated in the movement makes consumers feel as if they are feeling it, so in addition to the use of persuasive text, the use of onomatopoeia in advertising helps increase the attractiveness of products, especially in beauty.Keywords: onomatopoeia, diction, advertising, beauty, SENKA Perfect Whip